Constraints to Micro, Small and Medium Enterprises Recovery - Eluphy Banda Nyirenda; Abubaker Qutieshat (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: This review paper was done to understand the major constraints to Micro Small and Medium Enterprises’ (MSMEs) recovery in Malawi following the impact of COVID-19, discuss implications, and propose policy recommendations. Design/methodology/approach: A systematic review of literature, both grey and from peer reviewed journals was used to identify the major constraints exerted on MSMEs following the onset of COVID-19. Findings: The major constraints to MSMEs’ recovery include disruptions in supply chain, demand for increased use of technology and innovation, lack of access to capital on information on opportunities/ emerging markets, increased health and safety requirements. Research limitations/implications: The unavailability of data on MSMEs’ contribution to the growth and scholarly publication on pre- and post-recovery in Malawi. Practical implications: This study proposes review of fiscal and monetary policies to align with MSMEs growth needs. Originality/value: This is a review paper. Paper type: A literature review.